2019
DOI: 10.3390/met9010042
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Analysis on High-Temperature Flow Behavior of 3Cr-1Si-1Ni Ultra-High Strength Steel for Modeling of Flow Stress

Abstract: High-temperature plastic flow is the underlying process that governs the product quality in many advanced metal manufacturing technologies, such as extrusion, rolling, and welding. Data and models on the high-temperature flow behavior are generally desired in the design of these manufacturing processes. In this paper, quantitative constitutive analysis is carried out on 3Cr-1Si-1Ni ultra-high strength steel, which sheds light on the mathematic relation between the flow stress and the thermal-mechanical state v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…They concluded that MJC and MZA models showed good agreement against the experimental data except at low strain rates, however, overall strain-compensated AC displayed better correlation with the real data than others. Lei et al [15] conducted constitutive analysis to describe high temperature flow behavior of 3Cr-1Si-1Ni ultra-high strength steel and proposed an AC model that accounted strain compensation showed much capability in describing the material behavior at hot working conditions. He et al [16] verified existing flow stress models capability to capture the flow behavior in Ti2AlNb-based alloys and the constitutive equation displayed a more precise description against the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that MJC and MZA models showed good agreement against the experimental data except at low strain rates, however, overall strain-compensated AC displayed better correlation with the real data than others. Lei et al [15] conducted constitutive analysis to describe high temperature flow behavior of 3Cr-1Si-1Ni ultra-high strength steel and proposed an AC model that accounted strain compensation showed much capability in describing the material behavior at hot working conditions. He et al [16] verified existing flow stress models capability to capture the flow behavior in Ti2AlNb-based alloys and the constitutive equation displayed a more precise description against the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients of the relevant polynomial is shown in Table 3. Concerning the msA-type equation, the predicted stress can be obtained based on Equation (39), which is obtained by substituting Equation (38) in Equation (39). Figure 15 is shown the predicted stress from the modified strain-compensated Arrhenius-type (msA-type) equation.…”
Section: = + +mentioning
confidence: 99%
“…Therefore, 20Cr2Ni4A steel is widely applied to produce broad cross-section carburized parts. In previous research, there are many reports about the constitutive equation of metals and alloys at warm or hot temperatures [35][36][37][38][39]. The aim of the present study is that a higher-precision constitutive equation is established to describe the behavior of the 20Cr2Ni4A steel under a wider range, including warm forming and hot forming.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of experimental evidence has clearly shown that TMP parameters have a decisive effect on the deformation behavior of materials [24][25][26][27]. This study had a major focus on the cold rolling process, where the flow of a sheet is conditioned by roll gap geometry, straining levels and friction condition.…”
Section: Correlating the Flow-line Model Parameters With Roll Gap Geomentioning
confidence: 99%